Tron : Ares [videorecording (Blu-Ray)] - Wigutow, Jesse; DiGilio, David; Leto, Jared, 1971-; Lee, Greta, 1982-; Peters, Evan, 1987-; Turner-Smith, Jodie, 1986-; Minhaj, Hasan, 1985-; Castro, Arturo, 1985-; Anderson, Gillian, 1968-; Bridges, Jeff, 1949-; Monaghan, Cameron; Desjardins, Sarah, 1994-; et al. (Disney, 2026)
"When a highly sophisticated Program named Ares is sent from the digital world into the real world on a dangerous mission, it marks humankind's first encounter with A.I. beings."--